2014
DOI: 10.1038/ncomms6276
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy supports genomic stability by degrading retrotransposon RNA

Abstract: Many cytoplasmic substrates degraded by autophagy have been identified; however, the impact of RNA degradation by autophagy remains uncertain. Retrotransposons comprise 40% of the human genome and are a major source of genetic variation among species, individuals and cells. Retrotransposons replicate via a copy-paste mechanism involving a cytoplasmic RNA intermediate. Here we report that autophagy degrades retrotransposon RNA from both long and short interspersed elements, preventing new retrotransposon insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 47 publications
8
120
1
5
Order By: Relevance
“…Disused or aberrantly folded proteins are tagged with Ub signals that are subsequently sensed by UBD (Ub binding domain)-containing receptors to deliver them to the proteasome or the autophagosome during autophagy [26,31] (Figure 2). Similarly to the role of shuttling factors and proteasomal receptors in recognizing ubiquitinated substrates, autophagy relies on its own arsenal of autophagy receptors to recognize intracellular ubiquitinated aggregates (p62, NBR1, OPTN, TOLLIP) [32][33][34][35][36], bacteria (p62, OPTN, NDP52) [37][38][39], peroxisomes (NBR1) [40], mitochondria (OPTN, NDP52, Tax1BP1) [41][42][43], zymogen particles (p62) [16], proteasome (RPN10) [24], midbody (p62, NBR1) [15,44], or nucleic acids (p62, NDP52) [18,45] (Table 1), and link the material to autophagosomal membranes. Notably, the capacity of ubiquitinated proteins to form aggregates, and thus become autophagy substrates, has been shown to depend on Ub chain length [46].…”
Section: Regulation Of Selective Autophagy By the Ub Systemmentioning
confidence: 99%
“…Disused or aberrantly folded proteins are tagged with Ub signals that are subsequently sensed by UBD (Ub binding domain)-containing receptors to deliver them to the proteasome or the autophagosome during autophagy [26,31] (Figure 2). Similarly to the role of shuttling factors and proteasomal receptors in recognizing ubiquitinated substrates, autophagy relies on its own arsenal of autophagy receptors to recognize intracellular ubiquitinated aggregates (p62, NBR1, OPTN, TOLLIP) [32][33][34][35][36], bacteria (p62, OPTN, NDP52) [37][38][39], peroxisomes (NBR1) [40], mitochondria (OPTN, NDP52, Tax1BP1) [41][42][43], zymogen particles (p62) [16], proteasome (RPN10) [24], midbody (p62, NBR1) [15,44], or nucleic acids (p62, NDP52) [18,45] (Table 1), and link the material to autophagosomal membranes. Notably, the capacity of ubiquitinated proteins to form aggregates, and thus become autophagy substrates, has been shown to depend on Ub chain length [46].…”
Section: Regulation Of Selective Autophagy By the Ub Systemmentioning
confidence: 99%
“…Microprocessor, a nuclear complex of miRNA-processing enzymes, also recognizes and cleaves L1, Alu , and SVA transcripts, at least in vitro (97). The finding that L1 and Alu RNAs are enclosed within human cell autophagosomes has implicated autophagy (i.e., the delivery of cytosolic constituents to the lysosome) as another host defense mechanism that degrades retrotransposon RNAs (98). Indeed, mice lacking the critical autophagy gene, Atg6/Beclin1, are characterized by higher levels of retrotransposon RNAs and increased rates of genomic insertions (98).…”
Section: Host Defense Against Retrotranspositionmentioning
confidence: 99%
“…The finding that L1 and Alu RNAs are enclosed within human cell autophagosomes has implicated autophagy (i.e., the delivery of cytosolic constituents to the lysosome) as another host defense mechanism that degrades retrotransposon RNAs (98). Indeed, mice lacking the critical autophagy gene, Atg6/Beclin1, are characterized by higher levels of retrotransposon RNAs and increased rates of genomic insertions (98). Additionally, retrotransposition is restricted in both somatic and germ cells by members of the apolipoprotein B mRNA-editing enzyme 3 (APOBEC3) family (89, 99).…”
Section: Host Defense Against Retrotranspositionmentioning
confidence: 99%
“…Autophagy mainly consist of three types namely, micro, macro and chaperone mediated. Recent studies suggested the fourth autophagic mechanism, RNautophagy, to degrade retrotransposon RNA [18][19][20] related proteins-LAMP2B, SIDT2 were suppressed at 4 days post senescence, while were significantly upregulated in 12 days post senescence ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%